Царские династии России - Никишин Владимир Олегович (Детская энциклопедия РОСМЭН, 2015)
Экземпляры: Ф-31;Ф-32 (20180524) / Инвентарный номер: 92811 / Цена: / Авт.знак: Н 62 / ГРНТИ: 03.23 / ББК: 63.3(2)